Teachers’ Perception in Implementing Technology-Mediated Task-Based Language Teaching In SMPN 6 Singaraja - Tarigan, Elsaday Marsanda; Kusuma, I Putu Indra; Wahyuni, Luh Gede Eka (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research was conducted to explore in depth how teachers perceive the implementation of TMTBLT in Indonesian education, particularly in junior high schools, in the process of teaching English. This study employed descriptive qualitative methods where the researcher focused solely on observing the phenomena occurring in the field and presenting data non-numerically. The study took samples from teachers at SMP Negeri 6 Singaraja who teach English in the 7th grade. The sampling process used purposive sampling, where samples were selected directly in the field. The instrument used in this research was a questionnaire with a 4-point Likert scale ranging from strongly disagree to strongly agree. The instrument developed by the researcher covered how teachers use TMTBLT, the difficulties teachers experience when applying TMTBLT, and the solutions prepared by teachers. After completing the data collection process, the researcher then conducted a descriptive statistical analysis of the results obtained. The research findings indicate that teachers have a positive perception, stating that TMTBLT can assist them in the process of teaching English. With TMTBLT, teachers also say that they can build interaction with students, encourage students to be more active, and be willing to learn independently to solve problems. However, they still encounter challenges in several areas, such as insufficient school facilities, for example, an unstable Wi-Fi network. Teachers still cannot ensure that all students participate actively due to the relatively large class sizes. Nevertheless, they strongly agree that TMTBLT should be further developed to support the teaching and learning process, especially in the field of language